Satellitenbildkarte/Satellite Image Map 1:250 000 Annandagstoppane SS 28-30/3, Antarktis - Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie); Frankfurt am Main (Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie), Frankfurt am Main, 1989)
Satellite image map, Topographic map SS 28-30/3 Annandagstoppane; Satellite image mosaicking, Geocoding and Satellite image map compilation, see: Sievers, J., et al. (1989); Acquisition data of Landsat imagery: see map legend; Marked oversnow route (Dec 1985 to Feb 1988); Spot heights (in metres above msl) are taken from the Norwegian map series "Dronning Maud Land" 1:250 000; Inset maps: Location diagram, Indexes to adjoining sheets at 1:250 000 and 1:1 000 000 scales, Satellite image mosaic diagram displaying also the ground control used; Sources used for: Topographic information, Ground control, Generic terms of geographical names, Scientific references, see map legend; Series of 17 published maps at 1:250 000 scale based on the IMW map sheet numbering system: Trinity Peninsula SP 21-22/13, Adelaide Island and Arrowsmith Peninsula SQ 19-20/14, Kvitkuven SS 28-30/1, Skjoldet SS 28-30/2, Annandagstoppane SS 28-30/3, Borgmassivet SS 28-30/4, Vestfjella SS 28-30/5, Fossilryggen SS 28-30/6, Uhliggipfel SS 28-30/7, Neumayersteilwand SS 28-30/8, Mannefallknausane SS 28-30/9, Heimefrontfjella SS 28-30/10, Amelangplatte SS 28-30/11, Stancomb-Wills Ice Stream SS 28-30/13, Tottanfjella SS 28-30/14, Herzog-Ernst-Bucht ST 21-24/8 and ST 25-28/5, Filchnerschelfeis (Nordost) ST 21-24/12 and ST 25-28/9; Scale: 1:250000; Projection: Lambert Conformal Conic; Bounding Box: POLYGON ((-9 -72, -4.5 -72, -4.5 -73, -9 -73, -9 -72)); Datum: WGS72